Homogeneous dual-site P lattice doping in CdS quantum rods for visible-light photocatalytic water splitting. (20th July 2021) - Li, He; An, Hua; Chong, Ben; Yang, Guidong; Wang, Lianzhou
Graphical abstract: Highlights: A homogeneous dual-site P lattice doping in CdS nanorods is demonstrated. P is doped into both the substitution site of S and the interstitial site of CdS. The stronger reduction potential and longer lifetime of electron is achieved. Homogeneous dual-site P lattice doping enhances the photocatalytic H2 evolution. Abstract: Dual-site lattice doping in semiconductor materials is highly promising for photocatalysis as it can tune the sub-band electronic structure and charge distribution of the photocatalyst. However, it is challenging to precisely regulate the band structure by dual-site doping using the same heteroatom. Herein, we report the homogeneous dual-site P lattice doping in CdS quantum rods, i.e. P is homogeneously doped into both substitutional site of S and interstitial site, leading to negative shift of valence and conduction bands with extraordinary visible-light excitation efficiency. The electrons generated in the newly designed photocatalyst have strong redox potential in reducing H + into H2 in photocatalysis. By introducing nontrivial co-catalyst Ni3 C quantum dots onto the surface of P-CdS quantum rods, the apparent quantum efficiency of the catalyst achieves 15.7% at 435 nm, which is 5 times higher than that of pristine CdS.